Ngāokeoke Aotearoa: The Peripatoides Onychophora of New Zealand - Trewick SA; Koot EM; Morgan-Richards M (MDPI (Basel, Switzerland), 2024)
(1) Background: Originally described as a single taxon, Peripatoides novaezealandiae (Hutton, 1876) are distributed across both main islands of New Zealand; the existence of multiple distinct lineages of live-bearing Onychophora across this spatial range has gradually emerged. Morphological conservatism obscured the true endemic diversity, and the inclusion of molecular tools has been instrumental in revealing these cryptic taxa. (2) Methods: Here, we review the diversity of the ovoviviparous Onychophora of New Zealand through a re-analysis of allozyme genotype data, mitochondrial DNA cytochrome oxidase subunit I sequences, geographic information and morphology. (3) Results: New analysis of the multilocus biallelic nuclear data using methods that do not require a priori assumptions of population assignment support at least six lineages of ovoviviparous Peripatoides in northern New Zealand, and mtDNA sequence variation is consistent with these divisions. Expansion of mitochondrial DNA sequence data, including representation of all existing taxa and additional populations extends our knowledge of the scale of sympatry among taxa and shows that three other lineages from southern South Island can be added to the Peripatoides list, and names are proposed here. In total, 10 species of Peripatoides can be recognised with current data.
Keywords: Onychophora; Ooperipatellus; Peripatoides; allozyme; cryptic species; mitochondrial DNA; peripatus; velvet worm